The value of yeast culture and L-Lysine (amino acid) in a sorghum grain ration for finishing fall pigs in drylot - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Sorghum grain is deficient in the amino acid, lysine. This test was to determine the value of a lysine feeding supplement recently on the market. Cultured yeast also is a source of lysine. Three lots of 10 pigs were fed, free choice, whole sorghum grain with a mixed protein supplement. One lot received the whole sorghum grain and a mixed protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. To each ton of the supplement 27 pounds Aurofac and one half pound zinc oxide were added. A second lot was fed the same except that 100 pounds of yeast culture was added to each 500 pounds of protein mix. A third lot was fed as lot 1 except that 10 pounds L-lysine feeding supplement was added to each ton of supplement.
Keywords: Swine; Yeast culture; L-lysine; Sorghum grain